2015
DOI: 10.1007/s11746-015-2751-z
|View full text |Cite
|
Sign up to set email alerts
|

Soy Protein–Gum Karaya Conjugate: Emulsifying Activity and Rheological Behavior in Aqueous System and Oil in Water Emulsion

Abstract: polydispersity (span) and the highest emulsifying activity among all native, mixed and conjugated polymers. Therefore, the percentage of gum karaya used for production of O/W emulsion can be decreased by partially replacing it with the conjugated gum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 39 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…The independent variables were X 1 : FG:SPI ratio (3:1-1:1), X 2 : pH (3-9), and X 3 : temperature (65-85 °C) while the dependent variables for this study were turbidity, emulsifying properties (emulsifying capacity and emulsion stability) and flow properties (flow behavior index and apparent viscosity at 10 s -1 ). The range for each response was set based on several previous studies (Hefnawy & Ramadhan, 2011;Nui et al, 2014;Shekarforoush et al, 2016;Hasanvand et al, 2018). The type of experimental design used was a face-centered central composite design (CCD) using a response surface methodology with six replications at the center.…”
Section: Experimental Design and Statistical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The independent variables were X 1 : FG:SPI ratio (3:1-1:1), X 2 : pH (3-9), and X 3 : temperature (65-85 °C) while the dependent variables for this study were turbidity, emulsifying properties (emulsifying capacity and emulsion stability) and flow properties (flow behavior index and apparent viscosity at 10 s -1 ). The range for each response was set based on several previous studies (Hefnawy & Ramadhan, 2011;Nui et al, 2014;Shekarforoush et al, 2016;Hasanvand et al, 2018). The type of experimental design used was a face-centered central composite design (CCD) using a response surface methodology with six replications at the center.…”
Section: Experimental Design and Statistical Analysismentioning
confidence: 99%
“…Kaushik et al (2015) and Bi et al (2013) have also demonstrated that a mixture of flaxseed gum and SPI could act as effective emulsifying and thickening agents. Furthermore, there are other studies on the interactions of SPI with other gums such as gum karaya (Shekarforoush et al, 2016) and gellan gum (Vilela et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The formation of conjugation occurs through a covalent linkage established between the carbonyl group present in the polysaccharide and the amine group located in the protein [ 16 ]. The Maillard reaction is a thermal process that begins with the production of a Schiff base, proceeds with the generation of ketamine from the Maillard reaction through the rearrangement of Amadori, and culminates in the development of melanoidin, which is distinguished by its brown pigment [ 17 ]. Melanoidin formation sometimes leads to undesirable conditions, such as bitter taste and burning aroma [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that the protein-polysaccharide conjugates enhance solubility and emulsifying capabilities to a greater extent than independent use of protein independently [ 19 21 ]. The formation of protein-polysaccharide conjugates is affected by the type and proportion of proteins and polysaccharides and processing conditions, including reaction time and temperature [ 17 , 22 ]. This study used whey protein and soy protein, representing animal and plant protein, respectively.…”
Section: Introductionmentioning
confidence: 99%